Factors Influencing Audit Judgement: Literature Review - Nugraha, Ervan Reri; Nugrahanti, Trinandari Prasetya (West Science Accounting and Finance, 2025)
Misjudgment by the Auditor will affect the accuracy of the final opinion on the fairness of the financial statements. Therefore, the assessment has a significant influence on the final decision, which directly or indirectly will also affect the decisions to be taken by stakeholders. This study aims to empirically find out about Audit Judgment. The approach used is a literature review by examining eight main studies by exploring the results of previous studies on what impacts can affect Audit Judgment. The theoretical contribution includes increasing knowledge for readers and researchers, providing references for further research. Practically, this study is expected to provide insight to readers, especially auditors and stakeholders, that the ability to provide audit judgment is important